2006
DOI: 10.1007/s11434-006-2055-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation of human adipose-derived mesenchymal stem cells into endothelial-like cells

Abstract: The neovascularization of ischemic tissue is a crucial initial step for the functional rehabilitation and wound healing. However, the short of seed cell candidate for the foundation of vascular network is still a big issue. Human adipose tissue derived mesenchymal stem cells (hADSCs), which possess multilineage potential, are capable of adipogenic, osteogenic, and chondrogenic differentiation. We examined whether this kind of stem cells could differentiate into endothelial-like cells and participate in blood v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…Because the formation of a capillary-like network is the specialized function of endothelial cells [27,30,31] , the RCE cell line established here is indeed an endothelial cell line. This conclusion is coincident with that of human vascular endothelial cells differentiated from human adipose tissue derived mesenchymal stem cells reported by Guan et al [43] . Morphology recovery with 5% BCS-containing MEM medium showed that the morphology of the RCE cells recovered from fibroblastic to polygonal on day 7.…”
Section: Discussionsupporting
confidence: 92%
“…Because the formation of a capillary-like network is the specialized function of endothelial cells [27,30,31] , the RCE cell line established here is indeed an endothelial cell line. This conclusion is coincident with that of human vascular endothelial cells differentiated from human adipose tissue derived mesenchymal stem cells reported by Guan et al [43] . Morphology recovery with 5% BCS-containing MEM medium showed that the morphology of the RCE cells recovered from fibroblastic to polygonal on day 7.…”
Section: Discussionsupporting
confidence: 92%
“…6 In the present study, the differentiated ASC-EPCs had increased expression of CD34 and VEGFR2 as well as functional vascular characteristics. Some previous studies 25,26 revealed that human ASCs had a low level of expression of VEGFR2 and could gradually differentiate into endothelial-like cells with increased expression of CD34 and VEGFR2. Therefore, we termed endothelial-differentiated ASCs as ASC-EPCs.…”
Section: Discussionmentioning
confidence: 97%
“…As hAF-MSCs can give rise to osteogenic, chondrogenic, adipogenic, myogenic, endothelial, hepatic or neurogenic lineages (3) they have been shown to be effective in the treatment of many diseases (4). Due to the endothelial differentiation potential of MSCs, they have received a significant amount of attention as an autologous source for cell-based therapy in restoring endothelial functions and promoting vascularization (5,6).…”
Section: Introductionmentioning
confidence: 99%